Evaluation of the Bacterial Contamination of Well Waters and the Effects of Leaf Plant Extract of Melia Azedarach on Such Contamination - Saba Riad Khudhaier Al-Taei (Journal of Global Pharma Technology, 2016)
This work has been conducted to examine bioactivity of certain species of bacteria in well water samples collected from eight wells in Yusufiyah area southern Baghdad and to assess the effects of plant leaf extraction of Melia azedarach on these bacteria. Bacteriological properties such as total plate count cfu/ml, MPN/1.ml, Fecal Coliform, Fecal Streptococci, E. coli and Pseudomonas aeruginosa of well water samples have been evaluated in July and January 2017. Total numbers of bacteria in July was varied from 210 to 6070 CFU / ml while the total numbers of bacteria in January was ranged from 115 to 1300 CFU / ml. The local and international specifications MPN reached the upper limit for the preparation of the total coliform count in a manner most likely CFU / ml> 1600 (MPN) and have a minimum CFU / 900ml in July but in January, it has reached the upper limit of the number of total coliform manner that count the most likely CFU / 100 ml> 1550 (MPN) and minimum CFU / 100 ml 100 hence conclude that 87.5% of water wells in July and January. Well waters indicators fecal coliform bacteria and E. coli and fecal Streptococci contamination. However, the contamination with fecal coliform bacteria was considered as an acceptable because they are not exposed to any type of chlorination before consumption by users. The dried plant leaves of the Melia azedarach were extracted by using methanol alcohol and the bioactivity of this extract was evaluated with isolated bacteria. The results have showed that the effects of the extract depend on bacteria species and the extraction concentration used. However, it was found that the extract had significant bioactivity on bacterial contaminated water and such ability of methanol alcoholic extract may be due to the content of steroidal, phenols and tannins compounds in the examined plant leaves being very effective against microbes.Keywords: Bioactivity, Melia azedarach, Extraction, Bacterial contamination, Well water.